Banana Production Status and Its Role on Income Generation and Livelihood Improvement in Chitwan, Nepal - Adhikari, Aakash; Paudel, Bipul; Pokhrel, Ashim (International Journal of Applied Sciences and Biotechnology, 2022)
The demand of banana fruit is ever increasing and Nepal's Terai region has immense potential for this high value crop. Government has kept it at top most priority where it can be grown like Chitwan district. This study examined the banana production, problems of banana production and about the livelihood improvement of banana farmers in Chitwan district, Province No.3 of Nepal during the year of 2022. Tharu were the dominant ethnic group of these villages. The numbers of respondents selected for this study belong between 22-59 years old. The major occupation of these respondents was farming 91.4 percent and 8 percent were in other services. A survey was conducted from a representative sample size of 60 banana growers. The sample was selected by using simple random sampling technique. Banana producers of Chitwan district are taking good benefit from the banana fruit as income was higher than the cost. It was found that from 1 bigha farmers can have income of Rs 650000 with the cost of Rs 345000. It was found that among different sources of credit, people were mostly reliant on their own fund. People's participation in various social groups such as savings and credit group, farmers group, water user group, cooperatives and other social groups have increased over the time. To enhance more banana production quantity and quality major problems of farmers should be dealt with, which would help to increase their earning resulting in higher living standard day by day and that way we can encourage more production. Int. J. Appl. Sci. Biotechnol. Vol 10(2): 93-98.